Expression of the lacZ gene from two methanol-regulated promoters in Pichia pastoris. - Tschopp, J F (1987)
Two DNA fragments containing putative control regions regulating the expression of the alcohol oxidase (AOX) and dihydroxy-acetone synthase (DAS) genes from the methylotrophic yeast Pichia pastoris were used in the construction of vectors for the expression of the Escherichia coli lacZ gene. These vectors were transformed into P. pastoris host cells and employed in experiments to measure the control mechanisms employed by each promoter in the production of beta-galactosidase fusion products. Results in P. pastoris suggest that the processes used to regulate the expression of these gene fusions involve both repression/derepression and induction mechanisms. Expression of the AOX-lacZ and DAS-lacZ fusions was examined in Saccharomyces cerevisiae as well. Interestingly, beta-galactosidase was expressed in a regulated manner in the heterologous host.